Compact Flexible Asymmetric Coplanar Strip Fed Spiral Antenna - Reshma Lakshmanan, S. Mridula, Anju Pradeep, P. Mohanan (International Journal of Advanced Science and Technology, 2020)
A compact ﬂexible spiral antenna with Asymmetric Coplanar Strip (ACS) feed structure is presented in this paper. The proposed antenna is printed on a 50 µm ﬂexible dupont material with dielectric constant (εr) 3.5 and loss tangent (tanδ) 0.027. The overall dimension of antenna is 5 mm×11 mm×50 µm. The prototype is fabricated and its performance is veriﬁed. The antenna has a measured bandwidth (-10 dB) of 80 MHz, which can cover ISM 2.4 GHz and WLAN bands. To test the ﬂexibility of the antenna, the antenna is simulated in bent conﬁgurations of different radii. Flexibility studies reveal that the resonance is in the 2.4 GHz ISM band even after bending. The proposed ﬂexible spiral antenna is intended for use in sensor applications.